Architectural rhetoric and the iconography of authority in colonial Mexico - Barteet, C. Cody, author.
1 online resource.
Keywords: This book investigates the Casa de Montejo and considers the role of the building's Plateresque facade as a form of visual rhetoric that conveyed ideas about the individual and communal cultural identities in sixteenth-century Yucataan. C. Cody Barteet analyzes the facade within the complex colonial world in which it belongs, including in multicultural Yucataan and the transatlantic world. This contextualization allows for an examination of the architectural rhetoric of the facade, the design of which visualizes the contestations of autonomy and authority occurring among the colonial peoples.